2020
DOI: 10.1186/s42523-020-00037-5
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome and its potential role in paradoxical anaerobism in pupfishes of the Mojave Desert

Abstract: Background: Pupfishes frequently enter paradoxical anaerobism in response to endogenously produced or exogenously supplied ethanol in a dose-dependent manner. To decipher the role of the gut microbiota in ethanolassociated paradoxical anaerobism, gut microbial communities were depleted using a cocktail of antibiotics and profiled using 16S rRNA gene sequencing. Results: Compared to the control group (n = 12), microbiota-depleted fish (n = 12) spent more time in paradoxical anaerobism. Our analysis indicated th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Bacteroides have also been previously identified as degradators of BPA or other aromatic hydrocarbon degradation ( Comte et al., 2006 ; Yang et al., 2019 ). Cetobacterium most frequently occurs as gut microbes ( Sheng et al., 2010 ) and sludge microbes ( Song et al., 2015a ; Tian et al., 2020 ), which were previously found to be involved in the consumption of alcohols ( Bhute et al., 2020 ), fatty acids, and protein ( Hao et al., 2017 ). Recent studies also found the existence of Cetobacterium in sludge and landfill sites ( Song et al., 2015a ; Tian et al., 2020 ) and their abilities in degradation of surfactants ( Motteran et al.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteroides have also been previously identified as degradators of BPA or other aromatic hydrocarbon degradation ( Comte et al., 2006 ; Yang et al., 2019 ). Cetobacterium most frequently occurs as gut microbes ( Sheng et al., 2010 ) and sludge microbes ( Song et al., 2015a ; Tian et al., 2020 ), which were previously found to be involved in the consumption of alcohols ( Bhute et al., 2020 ), fatty acids, and protein ( Hao et al., 2017 ). Recent studies also found the existence of Cetobacterium in sludge and landfill sites ( Song et al., 2015a ; Tian et al., 2020 ) and their abilities in degradation of surfactants ( Motteran et al.…”
Section: Resultsmentioning
confidence: 99%
“…These results imply that the intestine of Nile tilapia might harbour more diversified microbial communities in addition to the microbial communities reported thus far. Patescibacteria and Dependentiae dominated the pupfish gut [ 44 ]. Patescibacteria is associated with biodegradable plastics such as polylactic acid [ 45 ], and has also been reported as a potential microbial bioindicator of phosphorus mining [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results imply that the intestine of Nile tilapia might harbour more diversi ed microbial communities in addition to the microbial communities reported thus far. Patescibacteria and Dependentiae dominated the pup sh gut [44]. Patescibacteria is associated with biodegradable plastics such as polylactic acid [45], and has also been reported as a potential microbial bioindicator of phosphorus mining [46].…”
Section: Discussionmentioning
confidence: 99%